OFFSHORING AND ITS PROSPECTS IN UKRAINE - Сухонос, О.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The paper attempts to effect qualitatively new type of modern economic on development of Ukraine. The modern world is amenable to transformation due to the discovery of new forms of cooperation which are closely linked to the Internet. The article concerns the specifics and characterization of new types of cooperation, in particular offshoring, examples of the operations of offshoring, the schemes and zones of offshoring, and the possible consequences and implications for Ukraine in the framework of the vector of development.